2017
DOI: 10.1161/atvbaha.117.309609
|View full text |Cite
|
Sign up to set email alerts
|

Lmo2 (LIM-Domain-Only 2) Modulates Sphk1 (Sphingosine Kinase) and Promotes Endothelial Cell Migration

Abstract: Objective Lim-domain only (Lmo)2 transcription factor is involved in hematopoiesis and vascular remodeling. Sphingosine kinase (Sphk)1 phosphorylates sphingosine to sphingosine-1-phosphate (S1P). We hypothesized that Lmo2 regulates Sphk1 to promote endothelial cell (EC) migration and vascular development. Approach and Results Lmo2 and Sphk1 knockdown (KD) were performed in Tg(fli1:EGFP)y1 zebrafish and in HUVEC. Rescue of phenotypes or overexpression of these factors were achieved using mRNA encoding Lmo2 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
(49 reference statements)
0
24
0
1
Order By: Relevance
“…Additionally, LMO2 has been shown to promote angiogenic traits in glioma stem cells [23]. It has been shown in zebrafish, that knockdown of Lmo2 , via morpholino, resulted in defective intersegmental vessels [24]. Lmo2 knockdown impaired migration of human umbilical vein endothelial cells (HUVECs) [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, LMO2 has been shown to promote angiogenic traits in glioma stem cells [23]. It has been shown in zebrafish, that knockdown of Lmo2 , via morpholino, resulted in defective intersegmental vessels [24]. Lmo2 knockdown impaired migration of human umbilical vein endothelial cells (HUVECs) [24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in zebrafish, that knockdown of Lmo2 , via morpholino, resulted in defective intersegmental vessels [24]. Lmo2 knockdown impaired migration of human umbilical vein endothelial cells (HUVECs) [24]. Furthermore, knockdown or overexpression of LMO2 decreased or increased, respectively, SK1 protein levels [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This applies to the paper by Matrone et al 1 in this issue of ATVB , where the authors' delineated a novel signaling pathway within the domain of endothelial migration. LIM domain only 2 (LMO2) was first discovered as a recurrent translocation partner of T-cell receptor (TCR) loci in a subset of patients with T cell acute lymphoblastic leukemia in 1981 2, 3 .…”
mentioning
confidence: 98%
“…Studies on LMO2 have now shown that LMO2 not only functions as a proto-oncogenic gene in T-cells but also in hematopoiesis, vascular remodeling and stem cell biology 4-9 . Matrone et al 1 showed that LMO2 levels in zebra fish embryos regulate intersegmental vessel (ISV) formation. The evidence for a migration defect is the absence of endothelial cells in ISVs in the elegant photomicrographs.…”
mentioning
confidence: 99%